2019
DOI: 10.1210/clinem/dgz298
|View full text |Cite
|
Sign up to set email alerts
|

Beta-1 and Not Beta-3 Adrenergic Receptors May Be the Primary Regulator of Human Brown Adipocyte Metabolism

Abstract: Purpose Brown adipose tissue (BAT) activation in humans has gained interest as a potential target for treatment of obesity and insulin resistance. In rodents, BAT is primarily induced through beta-3 adrenergic receptor (ADRB3) stimulation, whereas the primary beta adrenergic receptors (ADRBs) involved in human BAT activation are debated. We evaluated the importance of different ADRB subtypes for uncoupling protein 1 (UCP1) induction in human brown adipocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 55 publications
3
57
1
Order By: Relevance
“…In human brown adipocytes, the effects of isoprenaline on lipolysis and gene expression were due to β 1 ‐adrenoceptors, that we showed previously compensate for the lack of β 3 ‐adrenoceptors even in brown adipocytes derived from β 3 ‐adrenoceptor knockout mice 23 . However, care should be used when interpreting data derived from human brown adipocyte cell cultures, 33 as we have previously shown 34 that in general they express much lower levels of β 3 ‐adrenoceptor mRNA than native BAT. This may pose challenges when using immortalized human brown adipocytes to investigate the role of β 3 ‐adrenoceptors in human physiology.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In human brown adipocytes, the effects of isoprenaline on lipolysis and gene expression were due to β 1 ‐adrenoceptors, that we showed previously compensate for the lack of β 3 ‐adrenoceptors even in brown adipocytes derived from β 3 ‐adrenoceptor knockout mice 23 . However, care should be used when interpreting data derived from human brown adipocyte cell cultures, 33 as we have previously shown 34 that in general they express much lower levels of β 3 ‐adrenoceptor mRNA than native BAT. This may pose challenges when using immortalized human brown adipocytes to investigate the role of β 3 ‐adrenoceptors in human physiology.…”
Section: Discussionmentioning
confidence: 78%
“…Since cultured mouse brown adipocytes express β 1 ‐adrenoceptor mRNA, 10 it is likely that the residual responses to mirabegron in β 3 ‐adrenoceptor knockout mice are mediated by the β 1 ‐adrenoceptor. Interestingly, a recent paper 33 suggested that the β 1 ‐ and not the β 3 ‐adrenoceptor is the primary adrenergic regulator of human brown adipocyte metabolism. Using a human immortalized brown adipocyte cell model, they showed that mirabegron had no effect on lipolysis or on the expression of several genes including UCP1 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, whereas treatment with β 3 -adrenergic receptor (β 3 AR) agonists in mice is able to selectively stimulate BAT and protect against diet-induced obesity, these effects are not seen in humans at doses low enough to prevent cardiovascular side effects (26,27). Interestingly, a recent study found that the β 1 AR may be the predominant βAR in human BAT (28), highlighting another confounding issue when translating murine BAT studies to human biology. Other attempts to selectively activate thermogenesis through sympathomimetic drugs or mitochondrial uncouplers have not been successful (26).…”
Section: Bat In Humans-beige or Brown?mentioning
confidence: 99%
“…While well characterised in rodents, until recently BAT was thought only to be found in human infants, however BAT has been identified in the supraclavicular, axillary, and paraspinal regions of adult humans and retains its thermogenic function ( 5 ). BAT is stimulated by cold exposure which induces sympathetic activation of β3-adrenergic receptors [β3AR, and possibly β1AR and β2AR ( 6 , 7 )] which activates the inner mitochondrial membrane (IMM) transporter uncoupling protein 1 (UCP1) ( 8 , 9 ). UCP1 transports protons generated from the electron transport chain across the IMM in a process uncoupled from ATP synthesis, generating heat for non-shivering thermogenesis ( 10 ).…”
Section: Introductionmentioning
confidence: 99%